Dual-phase glass ceramics for dual-modal optical thermometry through a spatial isolation strategy. Issue 44 (3rd November 2021) - Li, Xinyue; Chen, Youli; Yang, Tao; Zhu, Yiwen; Mao, Qinan; Zhong, Jiasong; Li, Shichen
Abstract : Remarkable dual-modal luminescence is realized by dual-phase glass ceramics through a spatial isolation strategy. Abstract : Glass ceramics (GCs) can be an ideal medium for dopant spatial isolation, avoiding the adverse energy transfer process. Herein, a spatial isolation strategy is proposed and fulfilled by dual-phase GCs. Structural characterization performed by X-ray diffraction (XRD), transmission electron microscopy (TEM) and selected area electron diffraction (SAED), verified the successful dual-phase precipitation of tetragonal LiYF4 and cubic ZnAl2 O4 nanocrystals (NCs) among aluminosilicate glasses. Impressively, it is evidenced that intense blue upconversion (UC) emission of Tm 3+ and deep red DS emission can be attained simultaneously upon 980 nm NIR and 400 nm violet light excitation, respectively, owing to the extremely suppressed adverse energy transfer process between physically separated Tm 3+ and Cr 3+ . This also suggests the partition of Yb 3+ and Tm 3+ into LiYF4 and Cr 3+ into ZnAl2 O4 respectively. In particular, optical thermometry based on the fluorescence intensity ratio (FIR) of Tm 3+ and fluorescence lifetime of Cr 3+ of dual-phase GCs were also performed in detail, with the maximum relative sensitivity of 1.87% K −1 at 396 K and 0.81% K −1 at 503 K, respectively. As a consequence, such a spatial isolation strategy would provide a convenient route for application in optical thermometry and extend the practical application of GC materials.